Efficacy of Gradient Compression Garments in the Hours After Long-Duration Spaceflight - Lee, Stuart M. C.; Ribeiro, L. Christine; Laurie, Steven S.; Feiveson, Alan H.; Kitov, Vladimir V.; Kofman, Igor S.; Macias, Brandon R.; Rosenberg, Marissa; Rukavishnikov, Ilya V.; Tomilovskaya, Elena S.; Bloomberg, Jacob J.; Kozlovskaya, Inessa B.; et al. (Frontiers in Physiology, 2020)
The incidence of presyncopal events is high soon after a long-duration spaceflight; >60% of returning astronauts could not complete a 10-min 80° head-up tilt test on landing day (R+0) after ~6 months of spaceflight. The objective of this study was to demonstrate the ability of a lower body gradient compression garment (GCG) to protect against an excessive increase in heart rate and decrease in blood pressure during standing after long-duration spaceflight. METHODS: Eleven astronauts (9 M, 2 F) volunteered to participate. The stand test protocol consisted of 2 min of prone rest followed by 3.5 min of standing. Subjects completed 1 familiarization session and 2 preflight data collection sessions in standard clothing and three tests on landing day while wearing GCG. Postflight tests were conducted 1-4 h (R+0A), ~12 h (R+0B), and ~24 h after landing (R+0C). RESULTS: All astronauts completed the stand test preflight. Three astronauts were unable to attempt the stand test at R+0A, and one of these was unable to start the test at R+0B. One astronaut was unable to complete 3.5 min of standing at R+0B (test ended at 3.3 min). Review of the individual’s blood pressure data revealed no hypotension but the astronaut reported significant motion sickness. Of the astronauts who participated in testing on landing day, the heart rate and mean arterial pressures responses to standing (stand-prone) were not different than preflight at any of the postflight sessions. CONCLUSIONS: Wearing the GCG after spaceflight prevented the tachycardia that normally occurs while standing after spaceflight without compression garments and protected against a decrease in blood pressure when moving to the upright posture.